Biochar and Manure Applications Differentially Altered the Class 1 Integrons, Antimicrobial Resistance, and Gene Cassettes Diversity in Paddy Soils - Ali, Niyaz; Lin, Yinfu; Jiang, Ligeng; Ali, Izhar; Ahmed, Ishtiaq; Akhtar, Kashif; He, Bing; Wen, Ronghui (Frontiers in Microbiology, 2022)
Integrons are genetic components that are critically involved in bacterial evolution and antimicrobial resistance by assisting in the propagation and expression of gene cassettes. The current study aimed to investigate the impact of biochar and manure on integrons, their gene cassettes, and relative antimicrobial resistance in the paddy soil using molecular techniques such as quantitative PCR and clone library development. A randomized complete block (RCB) design with three replicates and a plot size of 3.9 m × 6 m (23m2) was set to test four different treatments, i.e. control (untreated), biochar (20 t ha-1), manure (15 t ha-1), and combination of biochar and manure (10+7.5 t ha-1). The results presented that the Class (CL1)integrons were found in all samples with higher concentration and abundance in manure treated plots compared to biochar treated plots. The gene cassette arrays in the field featured a broad pool of cassettes with a total of 35% novel cassettes. These encoded gene cassettes have their involvement to resist aminoglycoside, heat shock, heavy metals, and pilus secretory protein were abundant including twin-arginine translocase (Tat) A, B and C. Both in combination and solo treatments, the diversity of gene cassettes was increased in the manure enriched soil, however, biochar reduced the gene cassettes diversity and their array. Manure considerably enhanced abundance and antimicrobial resistance, whereas biochar amendment significantly reduced integrons and antimicrobial resistance. Moreover, biochar and manure have differential impacts on integrons and their gene cassette arrays where manure leads to an increase in the antimicrobial resistance and integrons, while biochar has a negative effect. Biochar, either alone or in combination with manure, could be a useful strategy to minimize antimicrobial resistance and microbial evolution in the environment, notably in paddy soils.